Winterwood - Ernshaw, Shea (New York : Simon Pulse, 2019)
"Rumored to be a witch, Nora Walker attempts to uncover the truth about a boy she discovers in the woods who went missing weeks ago during a brutal winter storm, only to learn that he wasn't the only one to go missing all those weeks ago"--
Keywords: Witchcraft -- Juvenile fiction; Magic -- Juvenile fiction; Time travel -- Juvenile fiction; Missing children -- Juvenile fiction; Forests and forestry -- Juvenile fiction; Witchcraft -- Fiction; Magic -- Fiction; Time travel -- Fiction; Missing children -- Fiction; Forests and forestry -- Fiction; Fantasy fiction